Frictional behavior of facing elements of geosynthetic reinforced soil retaining structures - Astarcı, Burak. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Geosynthetic reinforced soil retaining walls (primarily those with precast concrete block facing elements) reinforced by geogrids or geotextiles are in a period of enormous growth. The construction of geosynthetic reinforced soil retaining walls has gained popularity throughout the world and is becoming widespread in Turkey. Geosynthetic reinforced soil retaining walls with precast concrete block facing elements provide an aesthetically pleasing, cost-effective alternative that is easy to construct. In the construction, geosynthetic reinforcements are placed between the precast concrete block facing elements. This study investigates the friction between dry-stacked concrete blocks and different types of geosynthetic reinforcements used in geosynthetic reinforced soil retaining walls. Three types of polymer geosynthetic reinforcements are compared to one another with respect to their frictional properties with empty dry-stacked concrete blocks, sand used as infill, and gravel used as infill in the tests. The angle of friction was calculated for each case. The results were comparatively evaluated. The friction between concrete blocks and geosynthetic reinforcement is referred as the connection strength. An apparatus was developed to conduct a connection strength test. In this test, the tensile load applied on geosynthetic reinforcements was increased until complete pull-out occurred. The tests were repeated at different normal loads.
Keywords: Retaining walls.; Geosynthetics.; Friction.